Catur Purusa Artha Implementation In Supporting Business Sustainability - Mirah Ayu Putri Trarintya, Ni Luh Putu Wiagustini, Luh Gede Sri Artini, I Wayan Ramantha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
A significant decrease and increase in the level of VCI health, make Village Credit Institutions must maintain the sustainability of their business. This study aims to analyze and explain the implementation of strategic resources with Catur Purusa Artha, namely the concept of Balinese local culture that has been developed and has the same spirit as Profit, People, and Planet. The theoretical implications of this research are 1) developing the concept of Business Sustainability (implementation of Catur Purusa Artha) based on local Balinese cultural values developed earlier than modern theory 2) provides an empirical contribution to the Resource Based View (RBV) Theory, that not all non-financial strategic resources can improve financial performance. The practical implications of this research are, in essence, the management of Village Credit Institutions, Local Governments and Village Credit Institutions Empowerment Institutions need to maintain a balance between financial performance and business sustainability by making policies for assessing the sustainability of the Village Credit Institution's business performance and adding the distribution of profits and costs incurred for customary villages.